Gerenciamento das águas urbanas numa perspectiva constitucional do Parque Natural Aloízio Fontes dos Santos em São Cristóvão (SE) - Santos, Naiggel Mansell dos (2023)
The text of the 1988 Federal Constitution that deals with the right to an ecologically balanced environment (art. 225, CAPUT) emphasizes that legal protection has the functionality of delimiting the interests involved in the environmental management of the different areas of the country. In this sense, the research presented here performs a legal analysis of the ecologically balanced environment from the constitutional perspective for the management of the Municipal Natural Park Aloízio Fontes dos Santos located in the municipality of São Cristóvão (SE). Thus, this analysis of the relationship between society and the natural park made it possible to verify whether the interests of municipal governance are aligned with the city's master plan, regarding the sectoral environmental policy and the specificities found in the communities living around this conservation unit, especially concerning the existing socio-environmental conditions in the Natural Park. The specific objectives of the research are: a) to compare the socioenvironmental historical variants found in the community; b) identify governance interests and their influence on the processes of changing social paradigms; c) structure action protocols in order to find answers to socio-environmental problems in a Natural Park. For this reason, given the need to understand the relationship between society and the environment, this research will use the phenomenological method, which will make it possible to perceive the transformations resulting from the inseparable interaction between the community and the Municipal Natural Park. The research results indicated that the researched community is aware of the role it plays in the conservation of the environment and urban waters, but also indicate that the community intimately understands that the municipal public entity has an important role in the care and conservation of the environment within that park. This research is being elaborated with the purpose of producing a technical product that will be an e-book, in which action protocols will be presented that will make it possible to guarantee legal compliance regarding the maintenance of sustainable environmental care in a Municipal Natural Park.